Efektivitas Program Bantuan Sosial Tunai Pada Masa Pandemi Covid-19 Di Kelurahan Tanjung Barat Kota Jakarta Selatan Tahun 2022 - Aprillia, Cindy; Susetyo, Ivan Budi (Jurnal Ilmu Administrasi Publik, 2024)
The research in this thesis discusses the Effectiveness of the Cash Social Assistance Program During the Covid-19 Pandemic in Tanjung Barat Village, South Jakarta City in 2022. This research aims to measure how effective the policies that the government has designed are to fulfill and guarantee basic needs and improve the standard of living of the Indonesian people due to the pandemic that has hit all levels of society, and has had a significant impact on the lives of Indonesian people, especially from an economic perspective. From the results of a survey by the Central Statistics Agency (BPS) for the South Jakarta area, the unemployment rate increased during the Covid-19 pandemic, therefore the author is interested in researching the problems previously described. Because Tanjung Barat is one of the areas in South Jakarta City.The theoretical framework that the authors use in this research is Public Policy and Policy Effectiveness. Then the research method used by the author is a qualitative method with a descriptive approach, as well as data collection through interviews with several sources concerned, observation by looking at the phenomenon directly and literature study through books, journals, news, etc. Then the results of this study indicate that the provision of Cash Social Assistance (BST) during the Covid-19 pandemic in Tanjung Barat Village, South Jakarta City was appropriate or effective, according to the effectiveness indicator used by the author. However, there are still a number of residents who fall into the underprivileged category in Tanjung Barat Subdistrict, South Jakarta City, who have not accepted or can be said to have not accepted for one reason or another. However, overall the assistance program that has been carried out by the government can be said to be effective.